Comparison of radiation dose and image quality between flat panel computed tomography and multidetector computed tomography in a hybrid CT‐angiography suite. Issue 2 (10th January 2020) - Jones, Aaron K.; Odisio, Bruno C.
Abstract: The purpose of this study was to compare, using the same radiation dose and image quality metrics, flat panel computed tomography (FPCT) to multidetector CT (MDCT) in interventional radiology. A single robotic angiography system with FPCT was compared to a single MDCT system, both installed in a hybrid CT‐angiography laboratory and both operating under automatic exposure control. Radiation dose was measured on the central axis (Dc ) of a CT dosimetry phantom 30 cm in diameter and 60 cm in length using default protocols for FPCT and MDCT with the imaged length in MDCT matched to the field of view of FPCT. The noise power spectrum (NPS), modulation transfer function (MTF), and z‐axis resolution were measured using the same phantom. Iodine contrast to noise ratio (CNR) was also measured. Radiation dose (Dc ) was 41%–69% lower in MDCT compared to FPCT when default protocols and automatic exposure control were used. While spatial resolution could generally be matched with appropriate choice of kernel in MDCT, MTF dropped more quickly at higher spatial frequency for MDCT than FPCT. Image noise was 49%–120% higher for MDCT compared to FPCT for comparable in‐plane spatial resolution. Z‐axis resolution was slightly better for MDCT than FPCT, while iodine CNR depended on protocol selection. Radiation dose was much lower for MDCT compared to FPCT, but image noise was much higher. Matching image noise in MDCT to FPCT would result in similar radiation doses. Iodine contrast depended on dose modulation settings for MDCT.